Topical Clindamycin in the Treatment of Acne Vulgaris (KYAMC Journal, 2013)
This study was conducted to evaluate the efficacy, safety and adverse effects of topical clindamycin phosphate 1% lotion in treating acne vulgaris in a group of Bangladeshi people. This prospective study was undertaken in skin & VD out patient department of Rajshahi Medical college Hospital, Rajshahi. A total of 30 patients, 15 (50%) males and 15 (50%) females between ages 15 and 35 years (mean 18 years) with acne of grades I, II and III of duration